Influence of silver nanoparticles’ size on their direct interactions with doxorubicin and its biological effects - Grzegorz Gołuński; Kinga Konkel; Barbara Galikowska-Bogut; Patrycja Bełdzińska; Katarzyna Bury; Marcin Zakrzewski; Kamila Butowska; Rafał Sądej; Jacek Piosik (Scientific Reports)
Abstract Breast cancer is one of cancer’s most deadly varieties. Its variability makes the development of personalized therapies very difficult. Therefore, improvement of classic chemotherapy is still one of the important challenges of cancer research. We addressed this issue applying nanotechnology to verify the influence of silver nanoparticles (AgNPs) on doxorubicin (DOX) anticancer activity and assess if the size of AgNPs affects their interactions with DOX. We employed a broad spectrum of biophysical methods, characterizing 5 and 50 nm AgNPs interactions with DOX using UV–Vis spectroscopy, dynamic light scattering, fluorescence spectroscopy, and atomic force microscopy imaging. Biological effects of observed AgNPs-DOX interactions were assessed utilizing MTT and 3D Matrigel assays on SKBR3 and MDA-MB-231 breast cancer cell lines. Obtained results indicate direct interactions between AgNPs and DOX. Furthermore, AgNPs size influences their interactions with DOX, as evidenced by differences in the heteroaggregates formation observed in biophysical experiments and further supported by in vitro biological assays. We detected reduction of tumor cell viability and/or colony sizes of the analyzed cancer cell lines, registering differences linked to the observed phenomenon. However, the effects may be limited to the outer borders of the tumor microenvironment as evidenced by the 3D model. Summing up, we observed diverse patterns of interactions and biological effects for different sizes of AgNPs with DOX providing insight how the nanoparticles’ size affects their interactions with other biologically active compounds. Moreover, obtained data can be further used in experiments on the reduction of tumor size i.e. before the surgical intervention.